Cooled Radiofrequency Ablation Treatment of the Genicular Nerves in the Treatment of Osteoarthritic Knee Pain: 18‐ and 24‐Month Results. Issue 3 (14th November 2019) - Hunter, Corey; Davis, Tim; Loudermilk, Eric; Kapural, Leonardo; DePalma, Michael
Abstract: Objective: The primary objective of this observational, prospective, multicenter study was to evaluate the long‐term outcomes, including pain, function, and perceived effect of treatment, in subjects undergoing cooled radiofrequency ablation (CRFA) who have pain due to osteoarthritis (OA) of the knee. Methods: This analysis included a subset of subjects previously enrolled in a prospective, multicenter randomized study comparing the safety and effectiveness of CRFA and intra‐articular steroid injection in patients with knee OA through 12 months who were contacted to participate in this extension study. Subjects were enrolled if they agreed to participate in up to 2 additional follow‐ups, at 18 and 24 months. Results: Eighty‐three subjects from the 5 participating sites underwent CRFA during the original study and were contacted for this extension study. Of the 33 subjects enrolled, 25 were evaluated at 18 months after CRFA treatment, and their mean numeric rating scale (NRS) score was 3.1 ± 2.7, with 12 subjects reporting ≥50% pain relief compared to baseline. At 24 months, 18 subjects reported a mean NRS score of 3.6 ± 2.8, with 11 demonstrating ≥50% pain relief. Functional improvement as measured by the Oxford Knee Score continued to be present, with an overall mean change from baseline of 26.0 ± 9.6 points at 18 months and 29.9 ± 10.4 points at 24 months. Conclusion: In this subset of subjects from a randomized controlled trial, CRFA provided sustained pain relief, improved function, and perceived positive effect through 24 months for subjects with OA knee pain with no safety concerns identified.